An investigation of student capabilities in private higher education - Somerville, Fenella Alison (My University, 2017)
Higher education in South Africa in the 21st century faces the complex challenge of balancing the demands of the neo-liberal global agenda with meeting national goals and addressing individual student needs. Research reveals the current South African higher education system to be inefficient, characterised by high attrition and low success rates. This is despite major restructuring, new legislation and a committed focus on access and equality. Lack of government funding, inadequate capacity and public demonstrations of student frustration are indicative of a crisis. This study used the capability approach to investigate student experiences in a private higher education institution. Using a sequential explanatory mixed methods design within an interpretive paradigm, a broad survey was followed by in-depth individual interviews to understand the factors that enable and constrain first-year student opportunities and achievements. The study found that student access to and participation in higher education is strongly driven by aspiration, and supported by affiliations as well as students’ ability to reflect on their experiences. These capabilities foster identity, learning and agency. There are many personal, social and institutional factors that restrict student functioning. While these might constrain achievement and have the potential to foreshorten a student’s higher education career, students who are able to adapt and develop resilience to the particular challenges they face within their daily experience have further opportunities for realising their higher education aspirations. KEYWORDS: Capability Approach; Higher Education; Inclusion; Diversity; Capabilities
Thesis is submitted in partial fulfilment for the degree of Master of Education by combination of coursework and research to the Faculty of Humanities, School of Education at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Education--Higher--South Africa; Universities and colleges--South Africa